TANGGUNG JAWAB HUKUM ARSITEK TERHADAP KONSTRUKSI BANGUNAN YANG TIDAK SESUAI DENGAN PERENCANAAN - Ni Made Trisna Dewi (Fakultas Hukum Universitas Dwijendra, 2019)
In line with the Government's efforts to improve development in all areas, the built-up aspect of housing development continues to grow rapidly. Environmental problems that threaten and greatly endanger human life has been the emergence of threats and greater danger, so people began to learn the secrets of natural ecosystems and rules of order, to correct all mistakes and errors of attitude and actions of wrongdoing, also to prevent errors Furthermore. Architects perform the stages of the job. Ideally all the above stages are done for various types of buildings, from residential buildings to complex buildings of skyscrapers. Given the complexity of design and heavy responsibility, it is clear that the practice of architects can not be done by any expert. The expert must have an architectural education background, work experience (the more experience the higher his or her skills) and professional competence. These are the things that must be legally recognized through the Law-Ars. Recognition of the profession of architects. This is what prompted the authors interested in writing research with the title